2011
DOI: 10.1002/jbm.b.31952
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous membrane of nano‐hybrid poly‐L‐lactic acid/silica xerogel for guided bone regeneration

Abstract: Nanofibrous membranes, consisting of a poly(L-lactic acid) (PLLA)-silica xerogel hybrid material, were successfully fabricated from a hybrid sol using the electrospinning technique for guided bone regeneration (GBR) application. These hybrid nanofibers exhibited a homogeneous and continuous morphology, with a nano-sized dispersed silica xerogel phase in the PLLA fiber matrix. The mechanical properties, such as the tensile strength and the elastic modulus, were improved as the silica xerogel content increased u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…The hydrolyzed hybrids containing silica exhibited an expressive increase of T onset and T offset , as already described in the literature . This increase can be correlated to the sol–gel process, which creates a better interface between the organic and inorganic phases because this method results in a more homogeneous inorganic phase when compared to those obtained by traditional methods .…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The hydrolyzed hybrids containing silica exhibited an expressive increase of T onset and T offset , as already described in the literature . This increase can be correlated to the sol–gel process, which creates a better interface between the organic and inorganic phases because this method results in a more homogeneous inorganic phase when compared to those obtained by traditional methods .…”
Section: Resultssupporting
confidence: 74%
“…As for the oxides phases, it has been reported that silica exhibits the following absorption bands: at 800 and 1,070 cm −1 , corresponding to the deformation and stretching of the Si─O─Si groups, respectively; a band located at 950 cm −1 related to stretching vibration of the silanol (Si─OH) group, and finally, a wide band located near 3,400 cm −1 , corresponding to the intra‐ and intermolecular bonds between the silanol groups . Zirconia displays Zr─O absorption bands at 519 cm −1 and 795 cm −1 related to the bending vibrations of this group .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, considerable effort has been made to incorporate bioactive inorganic particles into PCL nanofibers for improving the biocompatibility in vitro and in vivo [21][22][23]. More recently, sol-gel derived silica has gained increasing interest as an alternative inorganic phase, since it can be homogenously hybridized with biodegradable polymers at the molecular level [24][25][26][27][28][29]. These organic/inorganic hybrids can more closely mimic the chemical composition and nanostructure of the native bone ECM, leading to significantly enhanced mechanical properties and biocompatibility [30].…”
Section: Introductionmentioning
confidence: 99%
“…Guided bone regeneration (GBR) is a procedure aiming for the reconstruction of impaired bone tissue, and has become increasingly popular in oral and maxillofacial surgery for augmentation of alveolar bone. [1][2][3][4] This technique makes use of a membrane barrier to direct the growth of neo-bone tissue while preventing the ingrowth of fibrous tissues to the bone defects. [5][6][7] In the past decades, a variety of barrier membranes, including non-absorbable, for example, polytetrafluoroethylene, and absorbable membranes, such as polyglycolic acid, poly (lactic acid), and collagen membranes, have been developed and applied for GBR techniques.…”
Section: Introductionmentioning
confidence: 99%